How Did the American Revolution Relate to the French? Richard Price, the Age of Revolutions, and the Enlightenment. (March 2022) - Clark, J. C. D.
Abstract : Richard Price (1723–91) is important in present-day historiography chiefly for the interpretation of two great revolutions, the American and the French. Recent studies have depicted him as insightfully forward-looking, a well-informed cosmopolitan, his thought providing an interpretive key to the Age of Revolutions, and so as a landmark figure of a singular Enlightenment. They have paid insufficient attention to his identity as a theologian, a Welsh-born Nonconformist minister of more defined outlook, spending his life in England and campaigning above all for the relief of Nonconformist grievances, picturing "tyranny" and "superstition" in conventional Nonconformist terms. This article offers a reconsideration of the significance of such a Price for the historical understanding of two major and (it contends) related problems: how did the American Revolution relate to the French in a supposed Age of Revolutions, and how should they be understood as putative episodes in the development of the Enlightenment?